?Grow? the College? Why Bigger May Be Far From Better - Gordon C. Winston (Williams College, Williams Project on the Economics of Higher Education (WPEHE), 2001)
This brief paper asks if the proposition that 'growth is good' applies with equal force to private business and to private colleges and universities. An increasing appreciation of the fundamental differences in economic structure between business firms and academic institutions suggests that it's easy to make costly mistakes if those differences are ignored and 'expanded sales' may often be one of them. The most fundamental problem rests, simply, on the fact that since the price paid by a college's customers covers only a fraction of the cost of providing their education, rather than yielding additional net revenues, enrollment expansion (other things equal) will generate additional uncompensated costs. Special circumstances can sometimes still justify increased enrollments, but they are circumstances very different from those facing a business firm.
Keywords: 330; Hochschule; Unternehmenswachstum; USA